Characterization of Gold-Sputtered Zinc Oxide Nanorods—a Potential Hybrid Material - Veeradasan Perumal; Uda Hashim; Subash C. B. Gopinath; Haarindraprasad Rajintra Prasad; Liu Wei-Wen; S. R. Balakrishnan; Thivina Vijayakumar; Ruslinda Abdul Rahim (Springer, 2024)
Generation of hybrid nanostructures has been attested as a promising approach to develop high-performance sensing substrates. Herein, hybrid zinc oxide (ZnO) nanorod dopants with different gold (Au) thicknesses were grown on silicon wafer and studied for their impact on physical, optical and electrical characteristics. Structural patterns displayed that ZnO crystal lattice is in preferred c-axis orientation and proved the higher purities. Observations under field emission scanning electron microscopy revealed the coverage of ZnO nanorods by Au-spots having diameters in the average ranges of 5–10 nm, as determined under transmission electron microscopy. Impedance spectroscopic analysis of Au-sputtered ZnO nanorods was carried out in the frequency range of 1 to 100 MHz with applied AC amplitude of 1 V RMS. The obtained results showed significant changes in the electrical properties (conductance and dielectric constant) with nanostructures. A clear demonstration with 30-nm thickness of Au-sputtering was apparent to be ideal for downstream applications, due to the lowest variation in resistance value of grain boundary, which has dynamic and superior characteristics.